Genotype-phenotype correlation in Jordanian children with genetically-proven familial Mediterranean fever: The effect of R202Q mutation - Eyad Altamimi; Dua` N. Samara; Dima Bani Issa; Saied Jaradat; Wail Hayajneh (Pediatrics and Neonatology)
Background: Familial Mediterranean fever (FMF) is a hereditary periodic fever syndrome inherited as an autosomal recessive pattern; nonetheless, patients with symptomatic heterozygous variants exist. This study aimed to review children with genetically-proven FMF, to describe their mutation maps and clinical characteristics, and to explore the genotype–phenotype correlation. Methods: Medical charts of pediatric FMF patients who were diagnosed by both genetic mutation and clinical criteria and followed up at our hospital were reviewed. Demographic and clinical data, results of MEFV genetic testing, procedures, concomitant medical conditions, disease severity, and treatment response were recorded and analyzed. Results: A total of 132 patients (71 females [54%]) were included in the final analysis. The average ages at presentation and diagnosis were 6.2 ± 3.1 and 7.6 ± 4.4 years, respectively. The most common clinical features were abdominal pain (n = 120, 91%), fever (n = 97, 73.5%), and arthritis (n = 75, 56.2%). Gastrointestinal endoscopy was the most frequently reported procedure (n = 27, 20.45%). The most common mutation was R202Q (n = 71, 53.8%), followed by E148Q (n = 36, 27.3%), M694V (n = 30, 22.7%), and V726A (n = 22, 16.7%). Two rare variants with potential pathogenicity were identified—namely, c.-15 and c.-330. A novel MEFV mutation (p. Lys629 Met) was noted. Abdominal pain, arthritis, arthralgia, and skin rashes were more common with the R202Q mutation. Patients with compound heterozygous mutations showed a higher rate of abdominal pain (94.1%) and exhibited the best response to colchicine (67.6%). Patients with complex alleles had the highest rate of fever (80%) and arthritis/arthralgia (70%). Conclusion: FMF is endemic in Jordan. Genetic testing is important in FMF evaluation; however, the genotype–phenotype correlation needs further study. The R202Q mutation is possibly pathogenic and is associated with the manifestation of the full spectrum of FMF features; hence, it needs to be considered in the diagnosis of FMF patients in Jordan.